(Re) Visiting and (Re) Constructing Meaning: The Case of a Canadian and a Zimbabwean Indigenous Peoples’ Folktale - Mabasa, Ignatius (Ethnologies, 2023)
Framed from an auto-ethnographic theoretical and conceptual point of entry, this paper intends to reflect on two Indigenous peoples’ folktales told by two raconteurs, Louis Bird, an elder and storyteller from the Swampy Cree Nation (Canada), and the author, who is an African (Shona) storyteller. The two tales are traditional and were handed down orally, which makes the date of their creation or context unknown. Yet, despite the huge geographical and geo-political situatedness between the Shona (Zimbabwe) and the Cree (Canada), it is elements of cultural parallelism in the worlds of the two stories that are striking as they seem to converge and comment on multiple conceptual and thematic strands such as belonging, dispossession, displacement, domination and destabilisation. Besides the remarkable way that they use time as a literary device, both stories seem to demonstrate the ability of traditional Indigenous tales to function as possible legitimate historical records that can possibly offer multiple readings that speak to different audiences beyond a group’s cultural context.